Caracterización demográfica de la provincia Guantánamo (2013-2017) / Demographic Characterization of the Guantánamo province (2013-2017) - Odalis Machandi Thomas; Sahilí Cristía Lara (Universidad de La Habana, 2020)
The study of the demographic variables (fertility, mortality and migration) allows to know the structure and a population's dynamics, as well as to identify the necessary resources for the projections of development plans and future actions after the population's well-being. The article has as objective to analyze the behavior of this variables in the county Guantánamo in the period 2013-2017. Some of the results of the investigation evidence that, the fertility is located below the substitution level with inferior oscillations to 2,1 children for woman; as long as the contribution in children of those smaller than 15 years overcomes the 20 births annually. On the other hand, in the variable mortality an alarming behavior, the TBM is not evidenced it varies between 6,7 and 7,3 died by each a thousand inhabitants; while the TMI maintains figures above 4,0 deaths for each thousand born alive. Regarding the migration the county Guantánamo can be classified as issuing territory, because the migratory balances along the period are negative; while, La Habana and Matanzas are the main counties selected as destination, in that order; not happening this way to Pinegrove of the River, territory of smaller predilection. An element to stand out is that, the county Guantánamo is located in the Group of Aging III (GE-III), when possessing more than the 60 year-old population's 15% and more, regarding the total. Resumen El estudio de las variables demográficas (fecundidad, mortalidad y migración) permite conocer la estructura y dinámica de una población, así como identificar los recursos necesarios para las proyecciones de planes de desarrollo y acciones futuras en pos del bienestar de la población. El artículo tiene como objetivo analizar el comportamiento de dichas variables en la provincia Guantánamo en el periodo 2013-2017. Algunos de los resultados de la investigación evidencian que la fecundidad se ubica por debajo del nivel de reemplazo con oscilaciones inferiores a 2,1 hijos por mujer; en tanto el aporte en hijos de las menores de 15 años supera anualmente los 20 nacimientos. Por su parte, en la variable mortalidad no se evidencia un comportamiento alarmante, la tasa bruta de mortalidad (TBM) varía entre 6,7 y 7,3 fallecidos por cada mil habitantes; mientras que la tasa de mortalidad infantil (TMI) mantiene cifras por encima de 4,0 defunciones por cada mil nacidos vivos. Respecto a la migración la provincia Guantánamo puede clasificarse como territorio emisor, pues los saldos migratorios a lo largo del periodo son negativos; mientras que La Habana y Matanzas son las principales provincias seleccionadas como destino, en ese orden; lo que no sucede con Pinar del Río, territorio de menor predilección. Un elemento a resaltar es que la provincia Guantánamo se ubica en el grupo de envejecimiento III (GE-III), al poseer más del 15% de la población de 60 años y más, respecto al total. Palabras clave: envejecimiento, fecundidad, migración, mortalidad, provincia Guantánamo